Combined wave ceramic capacitor material and preparation method thereof

Through the process of mixing and sintering of two-time mixing and sintering, the mixing and sintering steps of acidic and alkaline silica sols are used to solve the problems of breakdown strength and dielectric loss resistance of traditional ceramic capacitor materials, and a high density and low dielectric loss ceramic capacitor materials are achieved.

CN119638404AActive Publication Date: 2025-03-18SHANTOU RUISHENG ELECTRONICS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411901885.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Traditional barium titanate-based ceramic capacitor materials have low breakdown strength and large dielectric loss, making it difficult to meet the needs of miniaturized and ultra-thin capacitors.

Method used

The process of mixing and sintering of two times is adopted. First, the acidic silica sol and barium titanate are mixed with raw materials such as barium titanate, and then mixed with alkaline silica sol. Through ball milling and sintering, a ceramic capacitor material with high density is formed.

Benefits of technology

It significantly improves the breakdown strength of ceramic capacitor materials and reduces dielectric loss. It is suitable for the applications of miniaturized and ultra-thin ceramic capacitor materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203410530000081
    Figure BDA0005203410530000081
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic capacitor materials, and particularly relates to a combined-wave ceramic capacitor material and a preparation method thereof. The preparation method of the ceramic capacitor material provided by the invention comprises the following steps: mixing barium titanate, yttrium oxide, cerium oxide, manganese oxide, calcium oxide, acidic silica sol and water, and carrying out ball milling and drying; grinding and crushing the primary mixture, mixing with alkaline silica sol and water, and carrying out ball milling and drying; grinding and crushing the secondary mixture, and sintering for the first time; grinding and crushing the primary sinter, then adding absolute ethyl alcohol for ball milling, drying, grinding and crushing; mixing the ball-milled mixture with a binder, granulating, and carrying out compression molding to obtain a ceramic green body; and carrying out heat preservation on the ceramic green body, and then carrying out secondary sintering to obtain the ceramic capacitor material. According to the ceramic capacitor material prepared by the preparation method provided by the invention, the breakdown strength of the material can be effectively improved, and the dielectric loss of the material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic capacitor materials, and in particular relates to a combination wave ceramic capacitor material and a preparation method thereof. Background Art

[0002] Ceramic capacitors have good voltage resistance and high stability, and are widely used in power equipment, copy and printing equipment, laser equipment, aerospace equipment and other fields. As the core material of capacitors, ceramic capacitor materials determine the performance of capacitors. With the advancement of technology and the development of the times, the development trend of capacitors is towards miniaturization and ultra-thinness, which puts forward higher requirements on the breakdown strength and dielectric loss of ceramic capacitor materials.

[0003] Barium titanate (BaTiO3) has excellent strong dielectric properties and is one of the best choices for preparing ceramic capacitor materials. However, the traditional barium titanate-based ceramic capacitor materials have low breakdown strength and large dielectric loss, which is difficult to meet the actual production needs, so it is necessary to improve them. Commonly used improvement methods include using yttrium oxide, calcium oxide, etc. for doping modification, or optimizing the preparation process to achieve the purpose of improving the breakdown voltage of the material and reducing the dielectric loss. For example, the prior art adds sintering aids, such as silicon dioxide, during the material preparation process to prevent the grain growth of ceramic particles during the sintering process, improve its material density, and then improve the breakdown strength and dielectric loss of the material. However, the prior art generally mixes silicon dioxide powder directly with raw material powders such as barium titanate, and then obtains ceramic capacitor materials through processes such as pressing and sintering. Because the powder is easy to agglomerate, it is easy to cause uneven mixing of raw materials. Silicon dioxide, as a sintering aid, cannot fully play the role of the sintering aid during the sintering process, resulting in some grains being too large, affecting the breakdown strength and dielectric loss of the final material. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the ceramic capacitor material obtained by directly mixing, pressing and sintering the silicon dioxide sintering aid with barium titanate and other raw material powders in the preparation process of barium titanate-based ceramic capacitor materials has limited improvement in breakdown strength and dielectric loss, and further provide a combination wave ceramic capacitor material and a preparation method thereof.

[0005] In order to solve the above problems, the scheme of the present invention is as follows:

[0006] A method for preparing a ceramic capacitor material comprises the following steps:

[0007] 1) barium titanate, yttrium oxide, cerium oxide, manganese oxide, calcium oxide, acidic silica sol and water are mixed, ball-milled and dried to obtain a primary mixture;

[0008] 2) Grinding and crushing the primary mixture, mixing it with alkaline silica sol and water, ball milling, and drying to obtain a secondary mixture;

[0009] 3) Grinding and crushing the secondary mixed material and then sintering it for the first time to obtain a primary sintered product;

[0010] 4) grinding and crushing the primary sintered product, then adding anhydrous ethanol to carry out ball milling, drying after ball milling, grinding and crushing to obtain a ball milled mixture;

[0011] 5) mixing the ball mill mixture and the binder, granulating the mixture, and pressing the mixture to obtain a ceramic green body;

[0012] 6) The ceramic green body is kept warm, and then sintered for a second time to obtain the ceramic capacitor material.

[0013] Preferably, the pH value of the acidic silica sol is 2.5-2.8, and the mass content of silicon dioxide is 28-35%;

[0014] The pH value of the alkaline silica sol is 9.0-9.5, and the mass content of silicon dioxide is 15-20%.

[0015] Preferably, in step 1), the mass ratio of barium titanate, yttrium oxide, cerium oxide, manganese oxide, calcium oxide, acidic silica sol and water is 100:(3-3.1):(2.3-2.5):(0.5-0.8):(2.0-2.2):(1.8-2.0):(100-110).

[0016] Preferably, the first sintering temperature is 1020-1050°C and the sintering time is 3-5h;

[0017] In step 6), the holding temperature is 550-580° C., the holding time is 1-3 h, the second sintering temperature is 1200-1250° C., and the sintering time is 2.5-3 h.

[0018] Preferably, the average particle size of barium titanate is 200-250 nm.

[0019] Preferably, in step 1), the ball milling speed is 450-500 rpm, the ball milling time is 15-20 h, the drying temperature is 100-105° C., and the drying time is 10-15 h;

[0020] In step 2), the ball milling speed is 450-500 rpm, the ball milling time is 15-20 h, the drying temperature is 100-105 ° C, and the drying time is 10-15 h;

[0021] In step 4), the ball milling speed is 600-650 rpm, the ball milling time is 15-20 h, the drying temperature is 80-100° C., and the drying time is 5-10 h.

[0022] Preferably, the amount of water added in step 2) is 1-1.1 times the mass of barium titanate;

[0023] The mass ratio of barium titanate to alkaline silica sol is 100:(0.8-1).

[0024] Preferably, the amount of anhydrous ethanol added is 0.8-1.0 times the mass of the primary sintered material;

[0025] The step 4) further comprises the step of passing through a 150-200 mesh sieve after grinding and pulverizing.

[0026] Preferably, the binder is selected from a polyvinyl alcohol solution, the mass concentration of the polyvinyl alcohol solution is 10-14%, and the amount of the polyvinyl alcohol solution added is 18-22% of the mass of the ball-milled mixture;

[0027] The pressure in the compression molding step in step 5) is 200-240 MPa.

[0028] The present invention also provides a combination wave ceramic capacitor material, which is prepared by the above-mentioned preparation method. The ceramic capacitor material prepared by the present invention has good stability and high breakdown strength, and can be applied to combination wave ceramic capacitor materials.

[0029] The technical solution of the present invention has the following advantages:

[0030] The preparation method of the ceramic capacitor material provided by the present invention comprises the following steps: firstly, barium titanate, yttrium oxide, cerium oxide, manganese oxide, calcium oxide, acidic silica sol and water are mixed, ball-milled and dried to obtain a primary mixture; then, the primary mixture is ground and crushed, mixed with alkaline silica sol and water, ball-milled and dried to obtain a secondary mixture; then, the secondary mixture is ground and crushed, and first sintering is performed, the primary sintered product is ground and crushed, anhydrous ethanol is added for ball milling, and dried, the ball-milled mixture is mixed with a binder, granulated, and pressed to obtain a ceramic green body; the ceramic green body is heat-insulated, and secondarily sintered to obtain the ceramic capacitor material. The present invention adopts two mixing and two sintering processes in the preparation process of ceramic capacitor materials, wherein acidic silica sol is used in the first mixing process instead of silicon dioxide, and the sensitivity of barium titanate to acid is utilized to make the barium titanate more evenly dispersed in the acidic silica sol solution, and the obtained mixture is then mixed and ball-milled with alkaline silica sol, and the barium titanate and other raw materials are further dispersed while neutralizing the acid on the surface of the mixture, so that the mixing is more even, and then after sintering and other processes, silicon dioxide can effectively promote the generation of liquid phase, so that the liquid phase can be fully wrapped, the excessive growth of the crystal grains can be prevented, the material density is improved, the breakdown strength of the material is effectively improved, and the dielectric loss is reduced. DETAILED DESCRIPTION

[0031] The following examples are provided for further understanding of the present invention, but are not intended to limit the best mode of implementation and do not limit the scope of protection of the present invention.

[0032] The experimental steps or conditions not specified in the following embodiments of the present invention can be implemented according to the conventional experimental steps and conditions used in the existing literature in the field. The reagents or instruments used without specifying the manufacturer are all conventional reagents or instruments that can be purchased commercially.

[0033] Example 1

[0034] This embodiment provides a method for preparing a ceramic capacitor material, comprising the following steps:

[0035] 1) 100 g of barium titanate (average particle size of 230 nm), 3 g of yttrium oxide, 2.5 g of cerium oxide, 0.8 g of manganese oxide, 2.0 g of calcium oxide, 1.8 g of acidic silica sol (pH value of 2.8, silicon dioxide mass content of 30%) and 100 g of water were mixed, ball milled at a ball milling speed of 500 rpm for 15 h, and then dried at a drying temperature of 100° C. for 10 h to obtain a primary mixture;

[0036] 2) grinding and crushing the primary mixture, mixing it with 1 g of alkaline silica sol (pH value is 9.2, silicon dioxide mass content is 18%) and 100 g of water, ball milling at a ball milling speed of 500 rpm for 15 h, and then drying at a drying temperature of 100° C. for 10 h to obtain a secondary mixture;

[0037] 3) Grinding and crushing the secondary mixture, and sintering at 1050° C. for 3.5 h to obtain a primary sintered product;

[0038] 4) Grind the primary sintered material, then add anhydrous ethanol (the amount of anhydrous ethanol added is 0.8 times the mass of the primary sintered material) for ball milling, the ball milling speed is 600 rpm, the ball milling time is 15 hours, and after the ball milling is completed, dry (drying temperature is 80° C., drying time is 5 hours), grind and crush, and pass through a 150-mesh sieve to obtain a ball milled mixture;

[0039] 5) mixing the ball milled mixture and a polyvinyl alcohol solution (the mass concentration of the polyvinyl alcohol solution is 10%, and the amount of the polyvinyl alcohol solution added is 18% of the mass of the ball milled mixture) and granulating the mixture, and pressing the mixture at 230 MPa to obtain a ceramic green body;

[0040] 6) The ceramic green body is kept at 550° C. for 1 hour, and then sintered at 1200° C. for 2.5 hours to obtain the ceramic capacitor material.

[0041] Example 2

[0042] This embodiment provides a method for preparing a ceramic capacitor material, comprising the following steps:

[0043] 1) 100 g of barium titanate (average particle size of 230 nm), 3.1 g of yttrium oxide, 2.3 g of cerium oxide, 0.5 g of manganese oxide, 2.2 g of calcium oxide, 2.0 g of acidic silica sol (pH value of 2.8, silicon dioxide mass content of 30%) and 110 g of water were mixed, ball milled at a ball milling speed of 450 rpm for 18 h, and then dried at a drying temperature of 100° C. for 10 h to obtain a primary mixture;

[0044] 2) grinding and crushing the primary mixture, mixing it with 0.8 g of alkaline silica sol (pH value is 9.2, silicon dioxide mass content is 18%) and 110 g of water, ball milling at a ball milling speed of 450 rpm for 18 h, and then drying at a drying temperature of 100° C. for 10 h to obtain a secondary mixture;

[0045] 3) Grinding and crushing the secondary mixture, and sintering at 1050°C for 4.5h to obtain a primary sintered product;

[0046] 4) Grind the primary sintered material, then add anhydrous ethanol (the amount of anhydrous ethanol added is 1.0 times the mass of the primary sintered material) for ball milling, the ball milling speed is 650 rpm, the ball milling time is 15 hours, and after the ball milling is completed, it is dried (the drying temperature is 80° C., and the drying time is 5 hours), grind and crush, and pass through a 150-mesh sieve to obtain a ball milled mixture;

[0047] 5) mixing the ball milled mixture and a polyvinyl alcohol solution (the mass concentration of the polyvinyl alcohol solution is 10%, and the amount of the polyvinyl alcohol solution added is 18% of the mass of the ball milled mixture) and granulating the mixture, and pressing the mixture at 230 MPa to obtain a ceramic green body;

[0048] 6) The ceramic green body is kept at 550° C. for 1 hour, and then sintered at 1200° C. for 3.0 hours to obtain the ceramic capacitor material.

[0049] Comparative Example 1

[0050] This comparative example provides a method for preparing a ceramic capacitor material, comprising the following steps:

[0051] 1) 100 g of barium titanate (average particle size of 230 nm), 3 g of yttrium oxide, 2.5 g of cerium oxide, 0.8 g of manganese oxide, 2.0 g of calcium oxide, 0.54 g of silicon dioxide and 100 g of water were mixed, ball-milled at a ball-milling speed of 500 rpm for 15 h, and then dried at a drying temperature of 100° C. for 10 h to obtain a primary mixture;

[0052] 2) The primary mixture was ground and pulverized, mixed with 0.18 g of silicon dioxide and 100 g of water, and ball-milled at a speed of 500 rpm for 15 h, and then dried at a drying temperature of 100° C. for 10 h to obtain a secondary mixture;

[0053] 3) Grinding and crushing the secondary mixture, and sintering at 1050° C. for 3.5 h to obtain a primary sintered product;

[0054] 4) Grind the primary sintered material, then add anhydrous ethanol (the amount of anhydrous ethanol added is 0.8 times the mass of the primary sintered material) for ball milling, the ball milling speed is 600 rpm, the ball milling time is 15 hours, and after the ball milling is completed, dry (drying temperature is 80° C., drying time is 5 hours), grind and crush, and pass through a 150-mesh sieve to obtain a ball milled mixture;

[0055] 5) mixing the ball milled mixture and a polyvinyl alcohol solution (the mass concentration of the polyvinyl alcohol solution is 10%, and the amount of the polyvinyl alcohol solution added is 18% of the mass of the ball milled mixture) and granulating the mixture, and pressing the mixture at 230 MPa to obtain a ceramic green body;

[0056] 6) The ceramic green body is kept at 550° C. for 1 hour, and then sintered at 1200° C. for 2.5 hours to obtain the ceramic capacitor material.

[0057] Comparative Example 2

[0058] This comparative example provides a method for preparing a ceramic capacitor material, which differs from Example 1 in that in step 1), 1.8 g of acidic silica sol is replaced with 3 g of alkaline silica sol (pH value is 9.2, silicon dioxide mass content is 18%).

[0059] Comparative Example 3

[0060] This comparative example provides a method for preparing a ceramic capacitor material, comprising the following steps:

[0061] 1) 100 g of barium titanate (average particle size of 230 nm), 3 g of yttrium oxide, 2.5 g of cerium oxide, 0.8 g of manganese oxide, 2.0 g of calcium oxide, 1 g of alkaline silica sol (pH value of 9.2, silicon dioxide mass content of 18%) and 100 g of water were mixed, ball milled at a ball milling speed of 500 rpm for 15 h, and then dried at a drying temperature of 100° C. for 10 h to obtain a primary mixture;

[0062] 2) grinding and crushing the primary mixture, mixing it with 1.8 g of acidic silica sol (pH value is 2.8, silicon dioxide mass content is 30%) and 100 g of water, ball milling at a ball milling speed of 500 rpm for 15 h, and then drying at a drying temperature of 100° C. for 10 h to obtain a secondary mixture;

[0063] 3) Grinding and crushing the secondary mixture, and sintering at 1050° C. for 3.5 h to obtain a primary sintered product;

[0064] 4) Grind the primary sintered material, then add anhydrous ethanol (the amount of anhydrous ethanol added is 0.8 times the mass of the primary sintered material) for ball milling, the ball milling speed is 600 rpm, the ball milling time is 15 hours, and after the ball milling is completed, dry (drying temperature is 80° C., drying time is 5 hours), grind and crush, and pass through a 150-mesh sieve to obtain a ball milled mixture;

[0065] 5) mixing the ball milled mixture and a polyvinyl alcohol solution (the mass concentration of the polyvinyl alcohol solution is 10%, and the amount of the polyvinyl alcohol solution added is 18% of the mass of the ball milled mixture) and granulating the mixture, and pressing the mixture at 230 MPa to obtain a ceramic green body;

[0066] 6) The ceramic green body is kept at 550° C. for 1 hour, and then sintered at 1200° C. for 2.5 hours to obtain the ceramic capacitor material.

[0067] Test Example 1

[0068] The ceramic capacitor materials prepared in the above examples and comparative examples were subjected to performance tests (25° C., 1 KHz). The test results are shown in Table 1.

[0069] Table 1

[0070]

[0071] Obviously, for ordinary technicians in the field, other modifications can be made based on the above embodiments, and the obvious modifications brought about by these modifications are still within the protection scope of the present invention.

Claims

1. A method for preparing a ceramic capacitor material, characterized in that: The steps include: 1) barium titanate, yttrium oxide, cerium oxide, manganese oxide, calcium oxide, acidic silica sol and water are mixed, ball-milled and dried to obtain a primary mixture; 2) Grinding and crushing the primary mixture, mixing it with alkaline silica sol and water, ball milling, and drying to obtain a secondary mixture; 3) Grinding and crushing the secondary mixed material and then sintering it for the first time to obtain a primary sintered product; 4) grinding and crushing the primary sintered product, then adding anhydrous ethanol to carry out ball milling, drying after ball milling, grinding and crushing to obtain a ball milling mixture; 5) mixing the ball mill mixture and the binder, granulating the mixture, and pressing the mixture to obtain a ceramic green body; 6) The ceramic green body is kept warm, and then sintered for a second time to obtain the ceramic capacitor material.

2. The preparation method according to claim 1, characterized in that: The pH value of acidic silica sol is 2.5-2.8, and the mass content of silica is 28-35%; The pH value of the alkaline silica sol is 9.0-9.5, and the mass content of silicon dioxide is 15-20%.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the mass ratio of barium titanate, yttrium oxide, cerium oxide, manganese oxide, calcium oxide, acidic silica sol and water is 100: (3-3.1): (2.3-2.5): (0.5-0.8): (2.0-2.2): (1.8-2.0): (100-110).

4. The preparation method according to claim 1 or 2, characterized in that: The first sintering temperature is 1020-1050℃, and the sintering time is 3-5h; In step 6), the holding temperature is 550-580° C., the holding time is 1-3 h, the second sintering temperature is 1200-1250° C., and the sintering time is 2.5-3 h.

5. The preparation method according to claim 1 or 2, characterized in that: The average particle size of barium titanate is 200-250nm.

6. The preparation method according to claim 1 or 2, characterized in that: In step 1), the ball milling speed is 450-500 rpm, the ball milling time is 15-20 h, the drying temperature is 100-105° C., and the drying time is 10-15 h; In step 2), the ball milling speed is 450-500 rpm, the ball milling time is 15-20 h, the drying temperature is 100-105 ° C, and the drying time is 10-15 h; In step 4), the ball milling speed is 600-650 rpm, the ball milling time is 15-20 h, the drying temperature is 80-100° C., and the drying time is 5-10 h.

7. The preparation method according to claim 1 or 2, characterized in that: In step 2), the amount of water added is 1-1.1 times the mass of barium titanate; The mass ratio of barium titanate to alkaline silica sol is 100:(0.8-1).

8. The preparation method according to claim 1 or 2, characterized in that: The amount of anhydrous ethanol added is 0.8-1.0 times the mass of the primary sintered material; In step 4), after grinding and pulverizing, the product is screened through a 150-200 mesh sieve.

9. The preparation method according to claim 1 or 2, characterized in that: The binder is selected from a polyvinyl alcohol solution, the mass concentration of the polyvinyl alcohol solution is 10-14%, and the amount of the polyvinyl alcohol solution added is 18-22% of the mass of the ball-milled mixture; The pressure in the compression molding step in step 5) is 200-240 MPa.

10. A combination wave ceramic capacitor material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Base metal inner electrode multi-layer ceramic wafer type capacitor medium material prepared by chemical coating of water system

    CN101880167A

  • Zirconia ceramic bone implant and preparation method thereof

    CN109336592A

  • TiO2 (at) SiO2 (at) BaTiO3 composite ceramic powder material as well as preparation method and application thereof

    CN115565781A

  • Titanium compound modified silica-based composite material and preparation method thereof

    CN116122041A

  • Reduction-stable high dielectric constant ceramic material capacitors with nickel internal electrodes, comprises barium titanate core and mixed oxide shell components made using silica and boric acid sintering aid

    DE19918091A1